2000
DOI: 10.1177/014572170002600508
|View full text |Cite
|
Sign up to set email alerts
|

A Diabetes Management Program for African American Women With Type 2 Diabetes

Abstract: Participants found this program to be culturally relevant and acceptable. Its effects on diet, physical activity, and self-care behaviors will be assessed in a randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…were recruited from seven primary care practices in central North Carolina to participate in a randomized controlled trial of a diet and physical activity intervention (21,22). To participate, patients had to be African-American women, Ն40 years of age, with type 2 diabetes (defined as diagnosis of diabetes at Ն20 years of age with no history of ketoacidosis).…”
Section: Research Design and Methods -Study Participantsmentioning
confidence: 99%
“…were recruited from seven primary care practices in central North Carolina to participate in a randomized controlled trial of a diet and physical activity intervention (21,22). To participate, patients had to be African-American women, Ն40 years of age, with type 2 diabetes (defined as diagnosis of diabetes at Ն20 years of age with no history of ketoacidosis).…”
Section: Research Design and Methods -Study Participantsmentioning
confidence: 99%
“…The categories for the PA intervention were moderate intensity (e.g., walking briskly, mopping, raking lawn), mild intensity (slow walking, stretching exercises), non-weight bearing activities (stretching exercises), or no PA. Study design and intervention. The design of this study, a description of the intervention, and baseline characteristics of participants has been published elsewhere (16). The intervention, "A New Leaf.…”
mentioning
confidence: 99%
“…Selection of the CDAs is described elsewhere (16); all were African-American women with type 2 diabetes. One CDA was recruited from each participating practice site and trained for her role in this study during four weekly 4-h sessions.…”
mentioning
confidence: 99%
“…Previous studies have shown that traditional diabetes education, which includes content on recommended dietary changes, has not been successful in AA communities Keyserling, Ammerman et al, 2000). It has also been argued that one of the keys to reducing racial and ethnic health disparities is with culturally competent health care .…”
Section: Complications Due To Diabetes Are Numerous and Costly Compamentioning
confidence: 99%
“…In a meta-analysis dietary interventions overall reduced weight by 20 pounds and A1C by 2.7%-age points, on average (Brown, Upchurch, Anding, Winter, & Ramirez, 1996). Secondly, the use of traditional diabetes education that includes modifications in diet and nutrition without reference to cultural influences has been ineffective for AAW Keyserling, Ammerman et al, 2000). It has been proposed that the reason for unsuccessful results with generic education for this population was because the interventions were not culturally tailored and, in some cases, conflicted with cultural values.…”
Section: Gaps In the Literaturementioning
confidence: 99%